Heat-induced thrombosis extension after endovenous laser ablation: a clinical case - A. A. Fokin; D. A. Borsuk; A. V. Sazanov; H. P. Manjikyan (Кубанский научный медицинский вестник, 2020)
Endothermal heat-induced thrombosis (EHIT) is a complication of endovenous thermal ablation in treatment of varicose veins. Existing classiﬁcations do not account for the length of thrombus extension ﬂoating in the deep venous system. While the risk of extension is minor, the consequences can be baleful.Aim. To report a rare clinical case of endothermal heat-induced thrombosis extension formed in spite of ongoing anticoagulant treatment in a patient with endovenous laser ablation.Results. A 39 years-old man with endovenous laser ablation of the right great saphenous vein had class 2 EHIT with 1.92 cm length on the next day after surgery. Rivaroxaban was prescribed at a dose of 15 mg 2 times a day. EHIT extension above the inguinal ligament occurred on the 15th day after surgery, despite oral anticoagulant treatment. Open thrombectomy with high ligation was ordered. Postoperative period without complications. Preoperative Caprini score was 6 (varicose veins, BMI> 25 kg/m2 , minor surgery, personal history of venous thromboembolism (VTE)).Conclusion. The reported clinical case illustrates that both the choice of treatment strategy and follow-up of patients with EHIT need to account for the combined risk of embolism with existing EHIT and potential thrombus extension with subsequent massive embolism.